Risk factors for emergency cesarean delivery in patients with placenta accreta spectrum: a multicenter retrospective cohort study - Li, Min; Zhang, Hongyuan; Song, Xiao; Li, Liang; Meng, Fanqing; Chu, Ran (Frontiers in Medicine, 2025)
BackgroundPregnant women with placenta accreta spectrum (PAS), particularly those with placenta increta or placenta percreta, undergoing emergency cesarean section are at a high risk of excessive intraoperative hemorrhage and related complications. This study aimed to evaluate maternal and neonatal outcomes and to identify risk factors associated with emergency cesarean section in women with PAS.MethodsA multicenter retrospective cohort study was conducted, including PAS patients who underwent cesarean section at three tertiary hospitals between January 2016 and January 2023. After 1:1 propensity score matching (PSM), clinical characteristics were compared between the emergency and elective cesarean section groups using chi-square tests and nonparametric rank-sum tests. Risk factors for emergency cesarean section were identified through Cox proportional hazards regression analysis.ResultsAmong 299 patients included in the study, 78 were selected for analysis after PSM. In the matched cohort, patients in the emergency cesarean section group required significantly more packed red blood cell transfusions (p = 0.034), had a higher rate of ascending branch ligation of the uterine artery (p < 0.001), required more neonatal intensive care unit admissions (p = 0.041), and delivered neonates with lower birth weight (p = 0.044). Key risk factors for emergency cesarean section included a history of more than one prior cesarean section [hazard ratio (HR), 2.34; 95% confidence intervals (CI): 1.24–4.42], preoperative hemoglobin levels ≤100 g/L (HR, 2.28; 95% CI: 1.19–4.40), preeclampsia (HR, 2.93; 95% CI, 1.10–7.82), and vascular lacunae within the placenta (HR, 0.40; 95% CI, 0.21–0.76).ConclusionEmergency cesarean section in PAS patients is associated with increased transfusion requirements and adverse neonatal outcomes. Close monitoring and enhanced management of patients with identified risk factors may help improve maternal and neonatal outcomes.